1965
DOI: 10.1177/003072706500400503
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Development and Yield in the Potato

Abstract: In the potato plant there is competition for assimilates between foliage and tubers, and the balance can swing in one direction or the other depending on the treatments received. Skill in crop husbandry has found ways by which the crop can be manipulated towards higher returns. Growth analysis studies have now provided some understanding of the factors involved, better knowledge of which could lead to greater control over crop yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 2 publications
4
21
2
1
Order By: Relevance
“…This was also apparent at the second evaluation, but only in 1997. The greater amount of plant vegetative growth with early N application is consistent with results from several others (Ivins and Bremner 1965;Benepal 1967;Grewal et al 1979;Kleinkopf et al 1981;Vos 1995), who showed earlier tuberization and larger early-season allocation of carbohydrates to the tubers when N supply is low. The treatment effect on tuber number is less consistent in the literature as some researchers have also noted fewer tubers where N was applied (Sommerfeldt and Knutson 1968;Clutterbuck and Simpson 1978), whereas others observed tuber number increases (Hanley et al 1965;Dubetz and Bole 1975;Roberts et al 1982;Belanger et al 2002) or no change (Benepal 1967;Dyson and Watson 1971;De la Morena et al 1994) in tuber number with increasing N application rate.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This was also apparent at the second evaluation, but only in 1997. The greater amount of plant vegetative growth with early N application is consistent with results from several others (Ivins and Bremner 1965;Benepal 1967;Grewal et al 1979;Kleinkopf et al 1981;Vos 1995), who showed earlier tuberization and larger early-season allocation of carbohydrates to the tubers when N supply is low. The treatment effect on tuber number is less consistent in the literature as some researchers have also noted fewer tubers where N was applied (Sommerfeldt and Knutson 1968;Clutterbuck and Simpson 1978), whereas others observed tuber number increases (Hanley et al 1965;Dubetz and Bole 1975;Roberts et al 1982;Belanger et al 2002) or no change (Benepal 1967;Dyson and Watson 1971;De la Morena et al 1994) in tuber number with increasing N application rate.…”
Section: Resultssupporting
confidence: 89%
“…Overall, results from this experiment confirms the work of others that showed the need for an adequate amount of N sufficiently early in the season to set up the crop vegetatively to produce high yields (Ivins and Bremner 1965;Kleinkopf et al 1981;Roberts et al 1982;Westermann and Kleinkopf 1985). While applying some N at this time clearly delays tuberization, and in some cases appears to reduce tuber number and has the potential to increase N leaching, this infusion of early N seems to be required for the crop to attain its yield potential.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3). Also, tuber initiation makes diversion of assimilates to tuber, thus early tuber initiations cause small plants and leaf area leading to lower final yield (Ivins and Bremner, 1965;Bremner and Radley, 1966). Therefore, environmental conditions during the early growth (before tuber initiation and early tuber growth phase) may play crucial role for the late tuber growth.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in weight of a crop of potato tubers is usually a linear function of time when growing conditions remain constant (Beukema and van der Zaag 1990), with the rate of increase being relatively insensitive to environmental changes other than the supply of water (Moorby 1968). N supply influences both yield-determining factors, the bulking rate and the period of time of tuber growth (Ivins and Bremner 1965;Honeycutt et al 1996).…”
Section: Introductionmentioning
confidence: 99%